Digital Economy Report 2021 - United Nations Conference on Trade; Development (United Nations, 2021)
This publication takes stock of recent trends in the global data-driven digital landscape, examining opportunities and challenges for developing countries to benefit. It highlights the links to impacts of the Covid-19 pandemic, which led to an acceleration of digitalization trends and a significant increase in cross-border data flows. With a focus on the development perspective, it further considers the implications of cross-border data flows and their regulation, taking into account ongoing discussions and providing a review of the related literature. It looks at various policies that countries are applying with regard to cross-border data flows and explores advantages and disadvantages, particularly for developing countries, while also addressing the evolution of different approaches to regulation at the international and regional level. Finally, the report concludes with policy recommendations for establishing a balanced approach to facilitating progress in the productive regulation of cross-border data flows.